(3OQhS GdCUhds - (3GdCUagGfj, eMeO MSjf Hf Ydj CcHQ, cGf MqjG aj (B1248(3g`s ((3GHf cdH Ydj eMeO EHQGgje GdNhGfSGQjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B...(3CeG HYO dbO QJHJ gPG GdcJGH GdeUfa aj GdCUhd HGdOQhS Ydi ebOeI hefGgL hNGJeI(B...s
(3BNQgG (B:s
(3GfJgi hajg fXQ ef hLhg JXgQ(B... (3ajeG PcQfGg heG eQ aj GdeWdH GdChd(B...s
(3aj Chdg agQS dehVhYGJ GdcJGH, aQZ efg eDdag aj (B16 (3Pj GdMLI (B1248(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B254s
(3GdPQjYI(B:(3L(B8(3,U(B102(3,Qbe(B558s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3CUhd Gdabgs